Coevolutionary adaptation in mutualisms - Wyatt, G (2015)
Natural selection favours those individuals that respond best to novel features of their selective environment. For many, a critical challenge is responding to evolutionary change in mutualistic species. These responses create complex feedbacks, so only coevolutionary approaches are able to fully answer key questions about the maintenance or disruption of mutualistic behaviour, and explain the range of mechanisms that allow individuals to benefit from these associations. I first consider the hypothesis that economic models studying multiple classes of traders, where each trader seeks to optimise its own payoffs will yield insights into mutualistic systems. I show that individuals can be favoured to discriminate amongst potential partners based on the price for which they provide resources. Then, I show that market mechanisms can maintain cooperation and drive specialisation in mutualistic systems. I extend this market model to allow individuals to restrict a mutualistic partner's access to resources, and show that this strategy can stabilise cooperation and increase the fitness of both partners. I also explicitly incorporate relatedness in my market model. I show that high relatedness sometimes increases cooperativeness in members of a mutualistic species, but sometimes decreases cooperativeness as it narrow the scope for partner choice to maintain cooperation. Having studied market mechanisms, I consider indiscriminate costly help to members of another species. I discover that this trait can be favoured by natural selection and can be classified as either altruism between or altruism within species. Finally, I consider a framework for analysing coevolved phenotypic responses to a partner's cooperativeness, a challenging process to model. I demonstrate that this framework can yield firm predictions about behaviour whenever partners hold private information about their costs and benefits.